Ameliorating effect of Alstonia scholaris L. bark extract on histopathological changes following viper envenomation in animal models - Ghosh, Rituparna (Toxicol Rep, 2018)
OBJECTIVES: The primary symptoms associated with snake envenomation are both systemic and local. The local symptoms are characterized by pain, swelling, haemorrhage and myonecrosis at the site of bite. The present study investigates the ameliorating effect of the aqueous bark extract of Alstonia scholaris bark on viper venom induced histopathological and biochemical changes in liver and kidney of swiss albino mice models. METHODS & MATERIALS: Swiss albino mice (20 ± 2)g were treated with sublethal doses(0.5 μg and 1 μg) of Vipera russelli venom(VRV) intraperitonially The following groups were assigned in the study-Group I(saline control); Group II & III(Venom treated-0.5 μg ie ¼ LD50 and 1 μg ie 1/2 LD50) and Group IV &V(Venom-0.5 μg and 1 μg respectively incubated with Aqueous Alstonia scholaris (AAS) extract; 200 mg/kg bw) and Group VI (Antivenom serum (AVS) (2 mg/ml) followed by 1 μg Vipera russelli venom (VRV). The animals were sacrificed and their organs were immersed in Bouin's fixative for 24 h and stained with haematoxylin/eosin and observed under the microscope. The serum samples were collected from the animals and tested for serum Alanine transaminase (ALT) and Aspartate transaminases (AST) following the method of Reitman & Frankel(1957) and serum creatinine. RESULTS: The histological alterations observed in Group II and III liver sections were mainly pyknosis, karyorrhexis, cytoplasmic vacuolation, necrosis, fatty changes and hepatocytes atrophy. Sinusoidal dilatation, amyloidosis, portal vein thrombosis which was significantly reduced by AAS extract in Groups IV and V. A venom dose of 1 μg induced tubular cell acidophilia indicating cell damage, peritubular congestion, degenerating changes in the proximal tubules in the form of cytoplasmic vacuolations, partially destroyed bowman’s capillaries with dilated Bowman’s space in Group III that was significantly reduced by Aqueous Alstonia scholaris (AAS) (200 mg/kg bw) extract in Groups IV and Group V.AVS gave significant protection against venom induced action in Group VI. CONCLUSION: The present paper thus highlights the histopathological changes associated with Vipera russelli venom and systemic venom neutralization potential of Aqueous Alstonia scholaris (AAS) in animal models.